Assessing the Impact of Programming to Reduce the Stigmatization of Survivors of Sexual Violence in Eastern Democratic Republic of the Congo - Harvard Humanitarian Initiative (World Bank, Washington, DC, 2014)
This project rigorously evaluated programming that addresses stigma against survivors. In this program evaluation, the Harvard Humanitarian Initiative (HHI) worked with the Congolese NGO, Centre d Assistance Medico-Psychosociale (CAMPS) to assess which parts of their programming are most effective and how to continue to improve services related to reducing stigma. CAMPS is one of the most long established and wide-reaching providers of these services. With offices in some of the most conflict-affected and remote areas, working with CAMPS provides a unique opportunity to look at grass-roots models for addressing this issue.